Application of Certification Management Information Systems at LSP Engineering Hospitality Indonesia - Kadek Indah Melanie Dewi; I Wayan Gede Narayana; Rifky Lana Rahardian (Aptisi Transactions On Technopreneurship (ATT), 2023)
One of the problems that exist in the Hospitality Engineering Indonesia Professional Certification Institute is in terms of administration management which still uses conventional data and is inefficient in time, effort and cost in filling out the APL form and also the frequent loss of participant competency certificate archives because there is no specific system for managing data certification. The purpose of conducting this research is to help the management of the Engineering Hospitality Indonesia Professional Certification Institute find solutions to existing problems by building and implementing a Professional Certification Management Information System at the Indonesian Hospitality Engineering Professional Certification Institute which has a website platform. This research was conducted using the Waterfall Software Development Life Cycle (SDLC) method. This system is designed using Context Diagrams, Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD) and also this system is built with a website platform that uses the php programming language with the Laravel framework. In testing the system is done by blackbox testing and also distributing questionnaires to respondents as measured by a Likert scale to determine user acceptance of the information system. This system gets an average value of 85.8% based on measuring user acceptance of the system and it can be concluded that the Professional Certification Institute Certification Management Information System has been designed with "Very Good".